BURNOUT AMONG HEALTHCARE WORKERS: CAUSES, CONSEQUENCES, AND PREVENTION STRATEGIES – A SYSTEMATIC REVIEW - Laura Kurczoba; Aleksandra Oparcik; Anna Baranowska; Marta Cieślak; Anastazja Orłowa; Anita Pakuła; Klaudia Martyna Patrzykąt; Julia Pawłowska; Kinga Szyszka; Kamil Turlej (International Journal of Innovative Technologies in Social Science, 2025)
Background: Burnout has long been recognized as a critical occupational health issue, particularly within healthcare settings. Defined by emotional exhaustion, depersonalization, and reduced personal accomplishment, it emerges as a response to chronic work-related stress. Burnout is associated with substantial psychological, physical, and organizational consequences, including reduced job satisfaction, mental-health symptoms, and compromised patient safety. The COVID-19 pandemic intensified these risks by dramatically increasing workloads, accelerating organizational disruptions, and exposing healthcare professionals to prolonged stress and patient suffering. Objective: To synthesize recent evidence on the causes, consequences, and prevention of occupational burnout among healthcare professionals, and to evaluate implications for workforce wellbeing, healthcare quality, and organizational policy. Methods: A narrative review was conducted using PubMed, Scopus, and Google Scholar. Eligible publications included systematic reviews, meta-analyses, and observational studies examining determinants, outcomes, and preventive strategies related to burnout in healthcare workers. Keywords used in the search included: burnout, occupational stress, healthcare professionals, emotional exhaustion, depersonalization, mental health, COVID-19, resilience, organizational support, preventive interventions. Results: Across studies, burnout was consistently linked to a combination of individual, organizational, and environmental determinants. High workload, insufficient autonomy, inadequate managerial support, interpersonal conflict, and poor work–life balance emerged as key predictors. Consequences encompassed increased rates of depression, anxiety, chronic fatigue, sleep disturbances, absenteeism, staff turnover, and reduced quality of patient care. Evidence suggests that preventive strategies are most effective when integrating individual-level interventions—such as resilience training, stress-management techniques, and psychological support—with systemic measures including workload optimization, mentoring, flexible scheduling, and supportive leadership. Emerging digital tools, such as mobile mental-health applications and telemedicine-based support systems, show promise as complementary preventive resources. Conclusions: Burnout in healthcare professionals represents a multifaceted challenge with significant implications for individual wellbeing and healthcare-system performance. Comprehensive, multilevel prevention strategies—addressing both personal competencies and organizational structures—are necessary to mitigate its impact. Future research should prioritize longitudinal designs and systematic evaluations of innovative intervention models to inform evidence-based policy and to ensure sustainable workforce health.